Urban renewal on the historical downtown of Bogotá D.C. (Colombia). From the Santa Bárbara neighborhood to the Bronx, a displacement and gentrification legacy - Villegas, Guillermo; Villegas, Juan Guillermo (Geografares, 2017)
This paper is derived from a research project seeking to analyze the state of the art on urban gentrification in Colombia. A systematic literature review around displacement was carried out accompanied by a reference framework on gentrification, differential rent -rent gap– and real estate “mobbing”, which lead to a reinterpretation of such research works to conclude from these the use of a mechanism for displacement. Specifically, this study focuses on the experiences in neighborhoods in Bogota’s downtown; from the urban renewal in Santa Barbara (1980) qualified as immoral, to the interventions in Santa Inés -El Cartucho- (1998) and in Voto Nacional - El Bronx- (2016), whereupon, it was revealed a human instrumentation in the deployment of real estate “mobbing”, towards disguising displacement, devaluating properties, speculating with land and, in the meantime, encouraging gentrification. Keywords: Gentrification, rent gap, real estate mobbing.